2007
DOI: 10.1016/j.nlm.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhibition of calcineurin restores associative learning and memory in Tg2576 APP transgenic mice

Abstract: Misfolded amyloid beta peptide (Aβ) is a pathological hallmark of Alzheimer's disease (AD), a neurodegenerative illness characterized by cognitive deficits and neuronal loss. Transgenic mouse models of Aβ over-production indicate that Aβ-induced cognitive deficits occur in the absence of overt neuronal death, suggesting that while extensive neuronal death may be associated with later stages of the human disease, subtle physiological changes may underlie initial cognitive deficits. Therefore, identifying signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
126
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 39 publications
12
126
0
1
Order By: Relevance
“…The involvement of CaN in the neurodegenerative process and memory impairment in AD and PRE remains a controversial issue (Wang et al, 1999;Norris et al, 2005;Biasini et al, 2006;Dineley et al, 2007). In a previous study we demonstrated that Ab and PrP peptides trigger a caspase-3-dependent apoptotic neuronal death pathway, involving CaN and cyt c release from mitochondria (Agostinho and Oliveira, 2003).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The involvement of CaN in the neurodegenerative process and memory impairment in AD and PRE remains a controversial issue (Wang et al, 1999;Norris et al, 2005;Biasini et al, 2006;Dineley et al, 2007). In a previous study we demonstrated that Ab and PrP peptides trigger a caspase-3-dependent apoptotic neuronal death pathway, involving CaN and cyt c release from mitochondria (Agostinho and Oliveira, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…1). Accordingly it was reported that FK506 reduces the activity of this phosphatase in several brain regions of an AD mice model, improving the cognitive deficits observed in these animals (Dineley et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The level of CaN was found to be elevated in aged rats and in an APP transgenic mouse model of AD that display defects in cognition. 68,69 In the case of the transgenic mouse, the defects in cognition could be reversed by FK506, which is an inhibitor of CaN (Fig. 4).…”
Section: Alzheimer Diseasementioning
confidence: 97%
“…of the phosphorylated CREB was reduced and it was restored by treatment with FK506 (32). In the nuclear fraction of AD brains, a cleaved fragment of CaN (cCaN) is increased and the cleavage activates the phosphatase (33).…”
mentioning
confidence: 99%